DIFFERENTIAL DIAGNOSTIC CRITERIA FOR ACUTE BRONCHIOLITIS IN CHILDREN (World Bulletin of Public Health, 2025)
The article provides an overview of scientific articles on the diagnosis and differential diagnosis of bronchiolitis in young children. Acute bronchiolitis is an acute inflammatory disease of the lower respiratory tract with predominant damage to the small bronchi and bronchioles, developing mainly in infants. Acute bronchiolitis most often occurs in the 1st year of life in children (more than 80% of cases), 7-14% of them require inpatient treatment and is the most common cause of hospitalization in children under 2 years of age. all over the world. Some issues of differential diagnosis still remain problematic, especially the differential diagnosis of bronchiolitis and pneumonia caused by the respiratory synsitial virus.
Keywords: diagnosis; treatment